The fourth protocol - McKenzie, John; Axelrod, George (Great Britain : Rank Film Distributors, 1987)
KGB agent, Major Valeri Petrofsky has been reassigned at the request of the KGB Chairman for a secret mission, wherein he is sent to England to establish a residence near an American Military base and receive various items for couriers from the USSR. John Preston is the top British spy catcher, currently he is at odds with his superior cause, he doesn't lick his boots. After a recent operation caused his superior some embarrassment, he is reassigned to the menial task of overseeing airports and ports. One day one the couriers Petrofsky was expecting had an encounter with customs which left him dead. Preston then went through his things and found that he was carrying a thing that is part of an atomic bomb
Title from title screen
Executive producers, Frederick Forsyth, Wafic Said, Michael Caine ; music, Lalo Schifrin ; director of photography, Phil Meheux ; editor, Graham Walker
Cast: Michael Caine, Pierce Brosnan, James Edward Ross, Ned Beatty, Joanna Cassidy, Julian Glover, Michael Gough, Ray McAnally, Ian Richardson
DVD format
Keywords: Spy films